The regulation and self-control of advertising in Malaysia / Dr. Azizul Halim Yahya - Yahya, Azizul Halim (Dr.) (Faculty of Communication and Media Studies (FCMS), 2004)
In the era of globalisation and at the same time, in effort to develop and modernise the country, The Malaysian Government has pursued Western-style development policies. This means that the government is more tolerant especially in disseminating information, and especially in the broadcasting area. The change of policy dates from when the first private TV station was given permission to operate. However, this drastic change was only apparent at the beginning of 1994, when more private TV station licenses were issued and the ban on satellite dishes was lifted. However, the government realised that it had to take a cautious stance towards Western influence, which includes advertising and the media, since if left unregulated, it might harm Malaysian culture and lifestyle. In fact, Westerns influence on Malaysian advertising has been an issue since it was raised by the government in 1971. Minister of Special Functions and Information, the Honourable Ghazali Shafie, lamented that; "We note in our newspapers, magazines, radio and on television that the images created have very often little relation to our environment or what we hope to achieve in our society. There is...a certain degree of mindless aping of bourgeois values and styles of the West. I have noticed that certain products are associated through the mass media in this country with lifestyles of the middle and upper classes of the Wet, and this is being continuously presented to the Malaysian minds as something to model ourselves by." (Anderson,1984:219)